AGIRRE, Josean. Romain zen bere izena.: Elkar argitaletxea, Donostia, 2003 206 orrialde - Arozena, Ainhoa (EGAN, 2021)
AINHOA AROZENA: AGIRRE, Josean. Romain zen bere ¡zena. Elkar argitaletxea, Donostia, 2003 206 orrialde